Genotyping Points to Divergent Evolution of 'Candidatus Phytoplasma asteris' Strains Causing North American Grapevine Yellows and Strains Causing Aster Yellows - Davis, Robert E (Plant disease, 2018)
Grapevine yellows diseases occur in cultivated grapevine (Vitis vinifera L.) on several continents, where the diseases are known by different names depending upon the identities of the causal phytoplasmas. In this study, phytoplasma strains associated with grapevine yellows disease (North American grapevine yellows [NAGY]) in vineyards of Pennsylvania were characterized as belonging to 16S ribosomal RNA (rRNA) gene restriction fragment length polymorphism group 16SrI (aster yellows phytoplasma group), subgroup 16SrI-B (I-B), and variant subgroup I-B*. The strains (NAGYI strains) were subjected to genotyping based on analyses of 16S rRNA and secY genes, and to in silico three-dimensional modeling of the SecY protein. Although the NAGYI strains are closely related to aster yellows (AY) phytoplasma strains and are classified like AY strains in subgroup I-B or in variant subgroup I-B*, the results from genotyping and protein modeling may signal ongoing evolutionary divergence of NAGYI strains from related strains in subgroup 16SrI-B